Eudrilus Eugeniae As A Plug Flow Reactor - Mohaideen, Katheem Kiyasudeen Seeni (2018)
Earthworms are referred as ecological engineers and their guts are often compared to chemical reactors, however, modeling experiments to substantiate it are lacking. The aim of this study was to apply established reactor models on the gut of the composting earthworm Eudrilus eugeniae to better understand its digestive kinetics. Firstly, a mathematical model based on first-order kinetics was applied to determine the pattern of digestion rates of indicators, namely total carbon (%), total nitrogen (%), C/N ratio, 13C (‰), and 15N (‰) at 5 intersections (pre-intestine, foregut, midgut A, midgut B, and hindgut) along the gut of E. eugeniae. Secondly, an enzyme model of digestion and absorption was used to test two probable hypotheses, (i) digestion limitation, and (ii) absorption limitation to identify the mode of gut operation in E. eugeniae. To achieve that, the concentration profiles of crude protein (%) and 17 amino acids (%) were experimentally determined as substrate and breakdown products at the 5 intersections along the guts of E. eugeniae. The data then were used to determine the rates of digestion and absorption using the curve-fit simulation analysis. Lastly, a model based on deactivation kinetics was used to understand how three deactivation rates (β=0.05, 0.1, and 0.15) affect the rates of digestion at those 5 intersections along the gut. The experimental results based on the first-order model revealed that all the indicators exhibited a linear pattern of digestion along the gut, while, the enzyme model reflected that the rate of digestion to be higher than that of absorption. The deactivation model revealed that an increase in deactivation rates result in the reduction of digestion rates